Pengendalian Limpasan Air Hujan di Rusun Mahasiswa Kampus 2 Politeknik PU Semarang - Wildan Herwindo; Ingerawi Sekaring Bumi; Suhardi Suhardi; Syamsul Bahri; Andi Patiroi (Jurnal Konstruksi, 2023)
Flood events around the world tend to increase. Based on data from BNPB, floods in Indonesia are one of the disasters with the highest incidence. Flood disasters often occur in big cities in Indonesia such as Jakarta, Bandung, Samarinda and Semarang. Polytechnic of Public Works is a campus located in Semarang City and is a flood-prone area because it is situated on a lowland. Efforts are made to control rain runoff to reduce the potential for flooding on the PU Polytechnic campus. This study aims to determine the effectiveness of controlling rainwater runoff through the construction of infiltration wells in the student flats (flats) on campus 2 of the Public Works Polytechnic. The research was carried out by analyzing runoff discharge in the flat area and testing the soil permeability in that area. The research was conducted using quantitative methods using primary and secondary data. Primary data was obtained from soil permeability measurements while secondary data used included rainfall data, drainage master plans and Digital Elevation Model (DEMNAS) maps. Based on the research, the results obtained from measuring the permeability value of the soil in the PU Polytechnic flats area have a value of 0.029-1.680 cm/hour, which is included in low permeability. The results of soil permeability and geoelectrical tests showed that the soil conditions at the study site were water-saturated soils, making it difficult to absorb water into the soil. Analysis of the capacity of infiltration wells using a minimum permeability value of 0.029 cm/hour required 38,217 infiltration wells, while calculations with a maximum permeability value of 1.680 cm/hour required 660 infiltration wells. The number of needs for infiltration wells can be reduced by taking into account the volume of storage and the pattern of operation of the reservoirs in the student flat area of Campus 2 of the Public Works Polytechnic. The condition of the research location which is relatively saturated with water and has low permeability makes it difficult for water to absorb, so it is necessary to carry out further research to find other alternatives that are more suitable to be applied to that area.